1962
DOI: 10.1128/jb.84.5.896-901.1962
|View full text |Cite
|
Sign up to set email alerts
|

RELATIONSHIP OF HOST ANTIBODY TO FLUCTUATIONS OFESCHERICHIA COLISEROTYPES IN THE HUMAN INTESTINE

Abstract: A study was undertaken to determine the relationship of host antibody to the changes which take place among Escherichia coli serotypes present in the intestine. A survey of six healthy persons examined for E. coli monthly for 6 months reaffirmed the periodic fluctuations of antigenic types. Serotypes were studied from each individual and their appearance and maintenance or disappearance closely followed. Representative strains were chosen each month and used to prepare a heated sodium hydroxide lipopolysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1964
1964
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The immunoblot and the nitrocellulose paper carrying the '25I-labeled proteins were aligned exactly with the serrated edges before being placed on the X-ray film. a-hemolysin (4,7,15,19,20). It is also known that in humans, the level of these antibodies increases after E. coli infection.…”
Section: Discussionmentioning
confidence: 99%
“…The immunoblot and the nitrocellulose paper carrying the '25I-labeled proteins were aligned exactly with the serrated edges before being placed on the X-ray film. a-hemolysin (4,7,15,19,20). It is also known that in humans, the level of these antibodies increases after E. coli infection.…”
Section: Discussionmentioning
confidence: 99%
“…The production of colicines by strains of E. coli may be of some importance in maintaining them as resident strains (15), but, generally, this is not believed to be a major factor in the ability of a strain to establish itself as a resident (163,186,226). It was shown that host antibody to the E. coli strains involved plays no part in the phenomenon (61,163,175). Recently, an attempt was made to study this antagonism between certain strains of E. coli in vitro (220).…”
Section: Normal Bacterial Flora Of the Calf Intestine And Its Aberratmentioning
confidence: 99%
“…Antigenicaliy altered mutants are known to occur in bacterial infections (2,7,27) possibly as a result of the synthesis of antibody against certain surface antigens ofthe colonizing organisms (2). Antigenic, and other, properties, of bacterial cells may also change with varying environmental factors (32).…”
Section: Discussionmentioning
confidence: 99%